(untitled) (Journal of Science and Technology, 2016)
Historiography is primarily concerned with the history of history writing and this includes a critical examination and evaluation of the methods and sources of data of the histories and their makers. International Law, on the other hand, is a youthful discipline with a problem of placement. It is a branch of International Relations which is, itself, a branch of Political Science. But as a branch of law, a problem is created as to whether it is not proper, in looking at the history and historiography of International Law, to do so as part of the larger field of legal history. The pioneer historians and historiographers of the discipline did not do that.